Pengaruh Penerapan Bahan Ajar Berdiferensiasi Berbasis Multiple Intelligence terhadap Kemampuan Berpikir Kritis Peserta Didik - Laila Rahmah; Setiono Setiono; Billyardi Ramdhan (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Learning in the 21st-century era students are required to have critical thinking skills, but at the time these abilities were still in the low category. So we need a solution to overcome this problem. This study aims to determine the effect of applying differentiating learning materials based on multiple intelligences on students' thinking abilities. The method used is a quasi-experimental method with a non-equivalent control group design. The research subjects were students of class X SMA in Sukabumi City. The sampling technique used purposive sampling was 63 students, namely 32 in the experimental class and 31 in the control class. The instruments used are critical thinking skills test questions, and observation sheets using differentiated modules. The results of the study stated that the pretest-posttest value with an N-Gain calculation of 0.76 was in the high category with an average pretest-posttest value difference of 53.21. The limits of multiple intelligence are the two most dominant intelligence in the experimental class: linguistic intelligence and intrapersonal intelligence. Students with linguistic intelligence effectively use the differentiated module with an N-Gain value of 0.78 or in the high category. The average student response results in the use of differentiated teaching materials is 86.85 or in the very good category. The conclusions of this study, differentiated teaching materials based on multiple intelligences affect students' critical thinking abilities.